Perbandingan Aktivitas Antioksidan Ekstrak Biji Mangga Arumanis (Mangifera indica L.) Segar dan Kering dengan Metode DPPH (1,1 Diphenyl-2-picrylhidrazyl) - Ifmaily, Ifmaily; Juli Fendri, Sandra Tri; Husyalam, Mifta; Rahmawati, Annisa (Journal of Pharmaceutical and Health Research, 2024)
In previous research, the arumanis mango plant was proven to have antioxidant properties, because it contains secondary metabolites of flavonoids and tannins. Based on this research, arumanis mango seeds also contain flavonoids and have the potential to act as antioxidants. Arumanis mango seeds are a form of organic waste that is often thrown away after we eat arumanis mango fruit and have the potential to be used as a basic ingredient for making antioxidant products. The aim of this research was to determine the antioxidant activity and compare the antioxidant of fresh and dried arumanis mango seed extract samples using the DPPH (1,1-diphenyl-2-picryhydrazyl) method. The results obtained from the maximum absorption wavelength of DPPH are 518 nm, with an absorbance of 0.647. The results of comparative antioxidant activity for gallic acid obtained IC50 = 2.8997 µg/mL, and a sample of fresh arumanis mango seed extract with an IC50 value = 20.4806 µg/mL, and dried mango seed extract IC50 = 21.1501 µg/mL. Based on the research results obtained, the antioxidant activity of fresh and dried arumanis mango seed extract samples was classified as very strong (<50 µg/mL). The antioxidant activity of fresh extracted seed samples was higher than that of dried arumanis mango seed samples, because if IC50 higher, its mean antioxidant activity is lower.